2009
DOI: 10.1097/sap.0b013e3181953a49
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Breast Reconstruction

Abstract: Not all patients seeking autogenous breast reconstruction have sufficient donor tissue for a bilateral reconstruction. Identical twin isotransplantation, as a model system for allotransplantation without immunologic barriers, broadens the definition of "spare parts" surgery. In this case, we demonstrate the simultaneous transplantation of both autogenous and syngeneic deep inferior epigastric perforator flaps for bilateral breast reconstruction. As our understanding of immunology evolves, allotransplantation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…14 15 16 17 18 19 20 21 22 Compared to isogeneic solid organ transplants (SOTs), isogeneic soft tissue transplants are less frequently performed. Flap transplantation between monozygotic twins has been used for reconstruction of scalp, breast, and thoracic defects 2 3 4 5 6 7 8 ( Table 1 ). This is the fifth reported case of DIEP flap transfer for breast reconstruction in monozygotic twins, and the first to describe transplanting a bipedicled flap to reconstruct a unilateral breast.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…14 15 16 17 18 19 20 21 22 Compared to isogeneic solid organ transplants (SOTs), isogeneic soft tissue transplants are less frequently performed. Flap transplantation between monozygotic twins has been used for reconstruction of scalp, breast, and thoracic defects 2 3 4 5 6 7 8 ( Table 1 ). This is the fifth reported case of DIEP flap transfer for breast reconstruction in monozygotic twins, and the first to describe transplanting a bipedicled flap to reconstruct a unilateral breast.…”
Section: Discussionmentioning
confidence: 99%
“…This is the fifth reported case of DIEP flap transfer for breast reconstruction in monozygotic twins, and the first to describe transplanting a bipedicled flap to reconstruct a unilateral breast. 2 3 From an allogenic standpoint, myocutaneous flaps behave like vascularized composite allotransplants than SOTs; however, in the case of isogeneic transplant, immunosuppression is not needed. 23 Among the previously published flap transplantation cases, only one of the authors reported utilizing immunosuppression (1 month of short steroid taper) as recommended by their hospital's transplant service.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations